2012
DOI: 10.7314/apjcp.2012.13.6.2887
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Serum and Urine uPAR Levels for Diagnosis of Breast Cancer

Abstract: Malignant tumors have a capacity to degrade the extracellular matrix by controlled proteolysis. One system involved in these processes is the urokinase-type plasminogen activator (uPA) system. uPAR levels are elevated in tumors from several types of cancer. Our study was planned to investigate serum and urine levels of uPAR in breast cancer patients (n=180) and healthy controls (n=60) by ELISA. Serum (p<0.001) and urine (p<0.001) uPAR values in the patients were both significantly elevated. High serum and urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Urinary excretion of uPAR is considered a biomarker in urosepsis, 24 renal allograft rejection, 25 breast cancer, 26 and hematological malignancies, 27 but has similar [24][25][26] or weaker 18 association with disease severity or mortality than serum suPAR. A recent report in 86 renal transplant recipients showed that levels of urine, and not serum suPAR, were higher in patients with recurrent FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary excretion of uPAR is considered a biomarker in urosepsis, 24 renal allograft rejection, 25 breast cancer, 26 and hematological malignancies, 27 but has similar [24][25][26] or weaker 18 association with disease severity or mortality than serum suPAR. A recent report in 86 renal transplant recipients showed that levels of urine, and not serum suPAR, were higher in patients with recurrent FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…Coordination of extracellular matrix (ECM) proteolysis and cell signaling by uPAR underlies its important function in cell migration, proliferation and survival. These attributes make uPAR an attractive therapeutic target in cancer treatment (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, suPAR has been found in the urine of healthy individuals, cancer patients, renal transplant recipients, patients with urosepsis and human immunodeficiency virus (HIV)‐infected patients . Urine suPAR levels have been reported to be elevated in patients with various malignancies, including acute myeloid leukaemia (AML), bladder, pancreatic and breast cancer and gynaecological malignancies . Furthermore, urine suPAR levels decreased during chemotherapy in AML patients and demonstrated prognostic value in patients with pancreatic cancer .…”
Section: Discussionmentioning
confidence: 99%